Effects of AST‐120 on muscle health and quality of life in chronic kidney disease patients: results of RECOVERY study. Issue 1 (3rd December 2021) - Cha, Ran‐hui; Kang, Seok Hui; Han, Mi Yeun; An, Won Suk; Kim, Su‐Hyun; Kim, Jun Chul
Abstract: Background: The prevalence of sarcopenia is increased with declining renal function. Elevated serum indoxyl sulfate levels are associated with poor skeletal muscle conditions. We aimed to determine the effects of AST‐120, the oral adsorbent of indoxyl sulfate, on sarcopenia and sarcopenia‐associated factors in chronic kidney disease patients. Methods: This was a 48 week, randomized controlled, parallel group, open‐label, multicentre trial ( n = 150). The participants were randomly assigned in a 1:1 ratio to the control (CON) and AST‐120 (Renamezin®, REN) groups. Outcome measurements were performed at baseline and every 24 weeks for 48 weeks. The primary outcome was gait speed difference ≥0.1 m/s between the two groups, and secondary outcomes included hand grip strength, muscle mass, and health‐related quality of life. Results: A difference of gait speed ≥0.1 m/s was not observed during the study period. The mean dynamic‐start gait speed in the REN group increased from baseline to 48 weeks (1.04 ± 0.31 to 1.08 ± 0.32 m/s, P = 0.019). The static‐start gait speed changed by −0.024 and 0.04 m/s ( P = 0.049) in the CON and REN groups over 48 weeks, respectively. Hand grip strength decreased during the first 24 weeks and did not significantly change over the next 24 weeks in either group. The proportion of low muscle mass or sarcopenia at baseline was larger in the REN group than in the CON group, but the difference attenuated over the study period [low muscle mass and sarcopenia in the CON and REN groups at baseline, 4.0% vs. 18.9% ( P = 0.004) and 2.7% vs. 13.5% ( P = 0.017); at 24 weeks, 2.9% vs. 13.6% ( P = 0.021) and 1.4% vs. 10.5% ( P = 0.029); and at 48 weeks, 7.6% vs. 12.9% ( P = 0.319) and 4.5% vs. 8.1% ( P = 0.482), respectively]. Bodily pain, vitality, symptoms/problems, and cognitive function in the REN group improved, while the quality of social interactions and the kidney disease effects in the CON group aggravated from baseline to 48 weeks. Interaction between time and group was evident only in symptoms/problems, cognitive function, and kidney disease effects. Conclusions: The addition of AST‐120 to standard treatment in chronic kidney disease patients did not make a significant difference in gait speed, although AST‐120 modestly had beneficial effects on gait speed change and quality of life and showed the potential to improve sarcopenia. (clinicaltrials.gov: NCT03788252).